ESTIMATION OF FORMATION CONDITIONS OF MINERAL MEGASYSTEMS FROM THERMODYNAMIC MODELING - Chudnenko K.V.; Avchenko O.V.; Aleksandrov I.A. (My University, 2007)
The temperature and pressure of the formation of mineral assemblages and composition of fluid are currently estimated largely with the method of phase correspondence [1, 2]. This method consists in calculation (on a thermodynamic or experimental basis) of a certain stoichiometric mineral reaction, end member relationship, or a complex of certain reactions that determine the PT parameters and fugacity of volatile components.